- #1

- 6

- 0

This is from Numerical analysis course (Legendre polynom) - they gave us the polynomial transformation from [-1,1] to [a,b] as: x = 2/(b-a) * z - (b+a)/(b-a)

what is the proof of this tranformation? where did it come from?

thanks

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter mercuryman
- Start date

- #1

- 6

- 0

This is from Numerical analysis course (Legendre polynom) - they gave us the polynomial transformation from [-1,1] to [a,b] as: x = 2/(b-a) * z - (b+a)/(b-a)

what is the proof of this tranformation? where did it come from?

thanks

- #2

pasmith

Homework Helper

- 1,991

- 625

This is from Numerical analysis course (Legendre polynom) - they gave us the polynomial transformation from [-1,1] to [a,b] as: x = 2/(b-a) * z - (b+a)/(b-a)

what is the proof of this tranformation? where did it come from?

thanks

That isn't the transformation from [-1,1] to [a,b]; it's the transformation from [a,b] to [-1,1].

As for where it comes from: set x = mz + c, and impose the conditions that x = -1 when z = a and x = 1 when z = b. That gives you two linear simultaneous equations for m and c:

[tex]

-1 = ma + c \\

1 = mb + c

[/tex]

Share: